Effects of the 2010 Haiti Earthquake on Women's Reproductive Health. Issue 1 (8th March 2016) - Behrman, Julia Andrea; Weitzman, Abigail
Abstract : This article explores the effects of the 2010 Haiti earthquake on women's reproductive health, using geocoded data from the 2005 and 2012 Haiti Demographic and Health Surveys. We use geographic variation in the destructiveness of the earthquake to conduct a difference‐in‐difference analysis. Results indicate that heightened earthquake intensity reduced use of injectables—the most widely used modern contraceptive method in Haiti—and increased current pregnancy and current unwanted pregnancy. Analysis of impact pathways suggests that severe earthquake intensity significantly increased women's unmet need for family planning and reduced their access to condoms. The earthquake also affected other factors that influence reproductive health, including women's ability to negotiate condom use in their partnerships. Our findings highlight how disruptions to health care services following a natural disaster can have negative consequences for women's reproductive health.